Second language writing anxiety, computer anxiety, and performance in a classroom versus a web-based environment - Dracopoulos, Effie; Pichette, François (Studies in Second Language Learning and Teaching, 2011)
This study examined the impact of writing anxiety and computer anxiety on language learning for 45 ESL adult learners enrolled in an English grammar and writing course. Two sections of the course were offered in a traditional classroom setting whereas two others were given in a hybrid form that involved distance learning. Contrary to previous research, writing anxiety showed no correlation with learning performance, whereas computer anxiety only yielded a positive correlation with performance in the case of classroom learners. There were no significant differences across learning environments on any measures. These observations are discussed in light of the role computer technologies now play in our society as well as the merging of socio-demographic profiles between classroom and distance learners. Our data suggest that comparisons of profiles between classroom and distance learners may not be an issue worth investigating anymore in language studies, at least in developed countries.